2000
DOI: 10.1021/ja994441y
|View full text |Cite
|
Sign up to set email alerts
|

TEM and Laser-Polarized 129Xe NMR Characterization of Oxidatively Purified Carbon Nanotubes

Abstract: Multiwall carbon nanotubes are produced by decomposition of acetylene at 600 °C on metal catalysts supported on NaY zeolite. The support and the metal are eliminated by dissolving them in aqueous hydrofluoric acid (HF). Two methods were used to eliminate the pyrolitic carbon:  oxidation in air at 500 °C and oxidation by potassium permanganate in acidic solution at 70 °C. The progress and efficacy of the purification methods are verified by TEM. The properties of the purified multiwalled carbon nanotubes are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 33 publications
(64 reference statements)
2
48
0
Order By: Relevance
“…17 O in contrast to Δδ induce (−22 ppm). In comparison, a maximum shift of 2 ppm was predicted for 13 C in methanol B. This is also confirmed by the change of charge density (Δρ) in Figure 5b.…”
Section: Chemical Shifts Of Adsorbed Molecules Inside Cntssupporting
confidence: 73%
See 1 more Smart Citation
“…17 O in contrast to Δδ induce (−22 ppm). In comparison, a maximum shift of 2 ppm was predicted for 13 C in methanol B. This is also confirmed by the change of charge density (Δρ) in Figure 5b.…”
Section: Chemical Shifts Of Adsorbed Molecules Inside Cntssupporting
confidence: 73%
“…The vector map of ring current provides an intuitive and insight view to understand the effect of CNTs. This effect results in a similar shielding effect for all nuclei, for example, 13 C, 1 H, and 17 O in three different molecules. Electronic structure analysis for the host−guest and the guest−guest interactions indicates that the electronic effect makes the significant contribution to the chemical shifts of the polarizable atoms (such as 17 O).…”
Section: Resultsmentioning
confidence: 61%
“…The pretreatments shorten the CNTs and lead to the partial oxidation of the CNTs to produce functional oxygenated groups at the open ends and defects along the sidewall, in particular, which dramatically modify the electronic and structural properties of the nanotubes. [42][43][44][45][46][47] As a consequence, also very similar to other kinds of carbon-based materials mentioned above, the CNTs generally bear some functional oxygenated groups, of which some are electroactive. Li et al have observed a pair of redox waves at purified CNTs and ascribed them to the redox process of oxygenated groups produced at the CNTs, as shown below.…”
Section: Electrochemistry Of Cntsmentioning
confidence: 90%
“…[60] Since that work, HP xenon has been used to study diffusion in confined spaces or porous media [61] , [62] , [63] ; image such systems as a function of gas flow [64] or 129 Xe chemical shift [65] ; or spectroscopically probe single-crystal surfaces [66] , liquid crystals, [67] or combustion processes. [68] However, the greatest body of materials-related work has concerned the effort to probe void spaces and surfaces in microporous or nanoporous materials with HP 129 Xe, thereby providing information about pore size, pore shape, and gas dynamics in: nanochanneled organic, organometallic, and peptide-based molecular materials [69] (including in macroscopically oriented single crystals [70] ); multi-walled carbon nanotubes [71] ; gas hydrate clathrates [72] ; porous polymeric materials and aerogels [73] ; metalorganic frameworks [74] ; calixarene-based materials and nanoparticles [75] ; organo-clays [76] ; mesoporous silicas [77] ; and zeolites and related materials [78] -efforts that have been aided by computational studies of xenon in confined spaces (e.g., Refs. [79] ).…”
Section: 1002/chem201603884 Chemistry -A European Journalmentioning
confidence: 99%